1988
DOI: 10.1038/ki.1988.204
|View full text |Cite
|
Sign up to set email alerts
|

Lupus nephropathy in New Zealand F1 hybrid mice treated by (-)15-deoxyspergualin

Abstract: The effect of (-)15-deoxyspergualin (15-dsp), a new immunosuppressant which was originally separated from the culture filtrate of a strain of Bacillus laterosporus, was evaluated in this study. Various doses of 15-dsp were subcutaneously administered to New Zealand black/white F1 hybrid mice (B/WF1) four times a week starting at 14 weeks of age, just prior to the onset of nephropathy. The life span of the treated animals, studied at 0.6 to 6.0 mg/kg body weights, compared with the control mice was significantl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(21 citation statements)
references
References 19 publications
1
20
0
Order By: Relevance
“…In a previous paper (Makino et al, 1987b), we showed a suppressive effect of DSP on the development of lupus glomerulonephritis in MRL/Jpr and male BXSB mice. Similar findings were reported in (NZB x NZW)FI mice by others (Okubo et al, 1988). In these studies, the drugs were given at an early stage of disease development.…”
Section: Immunofluorescencesupporting
confidence: 74%
“…In a previous paper (Makino et al, 1987b), we showed a suppressive effect of DSP on the development of lupus glomerulonephritis in MRL/Jpr and male BXSB mice. Similar findings were reported in (NZB x NZW)FI mice by others (Okubo et al, 1988). In these studies, the drugs were given at an early stage of disease development.…”
Section: Immunofluorescencesupporting
confidence: 74%
“…It has been well demonstrated that cyclosporin A (5, 6), FK506 (7), 15-deoxyspergualin (8,21) and steroids (22,23), which have immunosuppressive action, are effective on a variety of glomerular diseases. Therefore, it is consi dered from this finding that the antinephritic action of these drugs including acteoside may be also mediated by the suppression of the production of various cytokins (24)(25)(26) and down-regulation of adhesion molecules on endothelial cells (27).…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, there have been numerous reports that cyclosporin A (5, 6), FK506 (7) and 15-deoxy spergualin (8), immunosuppressive agents, inhibit the progression of glomerular lesions in nephritic rats. These findings suggest that suppression of the activation of the local cell-mediated immune response may be effective on glomerulonephritis.…”
mentioning
confidence: 99%
“…In animal models, mizoribine has shown a strong synergistic effect when used in combination with cyclosporine to prolong the survival of canine renal allografts (1)(2)(3)(4)(5), and rat cardiac and partial lung allografts (6). Mizoribine has also been used successfully as a primary immunosuppressive agent in human renal transplantation, with results comparable or supe-(EC 1 .2.1.14), an enzyme required for the synthesis of guanine nucleotides from IMP.…”
Section: Introductionmentioning
confidence: 99%